Comparative analysis of environmental awareness among students in senior high schools, vocational schools, and islamic schools: Implications for enhancing naturalistic intelligence - Diana Zulyetti; Depitra Wiyaguba; Lufri Lufri; Andromeda Andromeda; Fatni Mufit (Universitas Sebelas Maret, 2025)
Environmental awareness is crucial for fostering responsible behaviors towards the environment, and understanding the variations among different educational settings can inform targeted educational strategies. This study aims to examine differences in environmental awareness among students from three types of secondary educational institutions—Senior High Schools (SMA), Vocational Schools (SMK), and Islamic Senior High Schools (Madrasah Aliyah)—using a descriptive-comparative quantitative approach. Furthermore, it seeks to explore the implications of students’ environmental awareness on the development of their naturalistic intelligence, particularly through experiential learning activities that address real-world ecological challenges. Data had been collected using a structured questionnaire that had been compiled and analyzed using the RASCH program. Based on the results of the analysis using the Ministeps (RASCH) program, 25 items of the environmental awareness rating scale instrument were obtained from 240 subjects from senior high schools, vocational schools, and Madrasah Aliyah. The data analysis technique in this research applied Kruskal-Wallis. The result of this research showed that the level of environmental awareness of students in the public senior high school was higher than Madrasah Aliyah, followed by the vocational school. Increased environmental awareness has the potential to stimulate students' naturalistic intelligence, fostering a deeper understanding of ecological systems and promoting sustainable behaviours through experiential learning activities that address real-world environmental issues.